PELATIHAN PENULISAN RPP BERBASIS HOTS TERINTEGRASI PENGUATAN PROFIL PELAJAR PANCASILA BAGI MAHASISWA PRODI PGSD STKIP MELAWI - Mardiana Mardiana; Joni Albar (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2023)
The Training on Writing RPP (Lesson Plan) Based on HOTs (Higher Order Thinking Skills) Integrated with Strengthening the Profile of Pancasila Students is a program designed to enhance the competencies of students in the Primary School Teacher Education Program (PGSD) at STKIP Melawi. This training aims to provide students with the knowledge and skills to develop RPPs that promote higher-order thinking skills while integrating the values of Pancasila into the teaching and learning process. The training covers the concepts and principles of RPP based on HOTs, the identification of learning objectives related to HOTs, the development of teaching strategies that support HOTs, the assessment of HOTs achievement, and the integration of the Pancasila student profile in RPPs. Participants will learn how to identify and formulate learning objectives that are relevant to HOTs and select appropriate teaching strategies to develop students' higher-order thinking skills. Furthermore, participants will learn how to integrate the values of Pancasila into various aspects of RPPs, such as learning objectives, teaching strategies, achievement indicators, assessment methods, and learning activities. The training also addresses assessment methods that can be used to evaluate the strengthening of the Pancasila student profile during the teaching and learning process. It is expected that this training will provide significant benefits to PGSD students at STKIP Melawi. Students will gain a better understanding of RPP based on HOTs and how to develop students' higher-order thinking skills. Additionally, they will be able to integrate the values of Pancasila into their teaching practices, contributing to the development of students' character and fostering integrity and responsibility. Through this training, students are expected to apply the knowledge and skills acquired in their teaching practices. Through community engagement, they can make tangible contributions to improving the quality of education in schools and strengthen the understanding and practice of Pancasila values in society.